Asymmetric Price Reaction: Evidence from Emerging Capital Markets - Slamet Sugiri; Sumiyana Sumiyana (The Indonesian Journal of Accounting Research, 2013)
This study investigates if emerging capital markets react asymmetrically to earnings shocks and if either firm-specific or market-wide approach explains the asymmetric reaction. This study is important because stock prices in emerging capital markets might not reflect firms’ fundamental values. Using data from Indonesia, Malaysia, and Philippines stock exchanges for the period of 2002-2007, this study finds that (i) the negative earnings shocks result in a greater price reaction than do positive ones, (ii) the firm-specific approach explains the asymmetric price reaction, and (iii) the market-wide approach does not consistently explain the asymmetric price reaction. These findings indicate that investors are overly optimistic and that stock prices do not reflect firms’ intrinsic values.